Woman wrapped in American flag - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a woman wrapped in an American flag. She stands beside a banner that reads, "The lord is m[y] shepherd and knows I'm gay" at the National March on Washington for Lesbian and Gay Rights.